Marketing Strategy of Pertamina LPG 3 Kg Cucum Sumiati Gas Base to Increase Sales Volume in Ciapus Village, Banjaran District, Bandung Regency - Acu Kusnandar (Return : Study of Management, Economic and Bussines, 2024)
The 3 Kg LPG business is a type of cooperation business carried out by the government and entrepreneurs intended so that the distribution is right on target because 3 Kg LPG gas is a subsidized gas from the government. One of the distribution channels for marketing 3 Kg LPG gas is through bases in villages. This study is intends to determine how the marketing strategy carried out by the Pertamina LPG 3 kg Cucum Sumiati gas base in Ciapus Village, Banjaran District, Bandung Regency increases sales volume. In this study using a qualitative approach, data collection in this study was carried out by triangulation, namely interviews, direct observation and documentation, Data analysis techniques used in this study were by the stages of data collection, data reduction, data presentation and conclusions. The marketing strategy carried out by the 3 Kg LPG Gas Base Cucum Sumiati has yet to be effective because the sales volume has not been achieved in accordance with the expected target so that to increase its sales volume it must improve and develop its marketing strategy.